Chiral Optical Properties of Phenyloxazoline Derivatives that Appear Only in the Solid State (Eur. J. Org. Chem. 4/2014). Issue 4 (February 2014) - Hirayama, Masato; Kobayashi, Yuhei; Tanaka, Yuki; Sato, Tomohiro; Harada, Takunori; Tajima, Nobuo; Kuroda, Reiko; Fujiki, Michiya; Imai, Yoshitane
Abstract : The cover picture shows that a chiral oxazoline compound, 4‐(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzonitrile, derived from an amino acid emits circularly polarized luminescence (CPL). Unlike in the solution state, the CPL of the chiral oxazoline compound 4‐(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzonitrile, which contains one oxazoline unit, was successfully observed in the solid state. On the other hand, the CPL of the chiral oxazoline compound 1, 4‐bis(4‐isopropyl‐4, 5‐dihydrooxazol‐2‐yl)benzene, which contains two oxazoline units, could not be observed. Details are discussed in the article by Y. Imai et al. onp. 719 ff.